Conformational heterogeneity of the BTK PHTH domain drives multiple regulatory states - David Yin-wei Lin; Lauren E Kueffer; Puneet Juneja; Thomas E Wales; John R Engen; Amy H Andreotti (eLife, 2024)
Full-length Bruton’s tyrosine kinase (BTK) has been refractory to structural analysis. The nearest full-length structure of BTK to date consists of the autoinhibited SH3–SH2–kinase core. Precisely how the BTK N-terminal domains (the Pleckstrin homology/Tec homology [PHTH] domain and proline-rich regions [PRR] contain linker) contribute to BTK regulation remains unclear. We have produced crystals of full-length BTK for the first time but despite efforts to stabilize the autoinhibited state, the diffraction data still reveal only the SH3–SH2–kinase core with no electron density visible for the PHTH–PRR segment. Cryo-electron microscopy (cryoEM) data of full-length BTK, on the other hand, provide the first view of the PHTH domain within full-length BTK. CryoEM reconstructions support conformational heterogeneity in the PHTH–PRR region wherein the globular PHTH domain adopts a range of states arrayed around the autoinhibited SH3–SH2–kinase core. On the way to activation, disassembly of the SH3–SH2–kinase core opens a new autoinhibitory site on the kinase domain for PHTH domain binding that is ultimately released upon interaction of PHTH with phosphatidylinositol (3,4,5)-trisphosphate. Membrane-induced dimerization activates BTK and we present here a crystal structure of an activation loop swapped BTK kinase domain dimer that likely represents the conformational state leading to trans-autophosphorylation. Together, these data provide the first structural elucidation of full-length BTK and allow a deeper understanding of allosteric control over the BTK kinase domain during distinct stages of activation.